Clinical findings and treatment outcomes for cats diagnosed with patent ductus arteriosus in the UK: a retrospective study of 19 cases (2004–2012). (2nd July 2016) - Wustefeld‐Janssens, B. G.; Burrow, R.; Mõtsküla, P.; Martin, M.; Dukes‐McEwan, J.
Abstract : Patent ductus arteriosus (PDA) is infrequently reported in cats and represents between 1–7.3 per cent of left to right shunting cardiac congenital anomalies. The objective of this study was to report the presenting complaints, clinical examination findings, diagnostic findings, treatment outcomes and survival times in cats diagnosed with a PDA in the UK. Medical records from three major UK referral centres were searched for cats that were diagnosed with PDA from January 2004 to December 2012. Data obtained for analysis included: signalment, clinical examination findings including murmur characteristics, diagnostic imaging findings, treatment outcomes and survival times. Nineteen cats were included in the analysis. The most common reason for referral was investigation of an incidentally detected heart murmur without clinical signs (13/19; 68 per cent). Pulmonary arterial hypertension (PAH) was diagnosed in seven (37 per cent) cats and those cats with PAH were significantly more likely to present with signs of disease (P=0.004). Median survival time in cats that were diagnosed with PDA and died due to cardiac causes was 898 days (interquartile range 459–1011 days). The median survival time of those cats that had an additional congenital anomaly was significantly shorter to those cats without a congenital anomaly (P=0.008).